Pengaruh Ukuran Perusahaan, Kepemilikan Institusional, Dan Profitabilitas Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2016-2019 - Neny Winarti; Nur Hidayati; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study is to analyze how the influence of firm size, institutional ownership, and profitability on earnings management using a quantitative approach method. The population used is the manufacturing sector companies listed on the Indonesia Stock Exchange in 2016-2019 with a total of 182 companies. The sample used in this study used a purposive sampling technique so that based on predetermined criteria, 10 companies were selected as research samples. The data collection method used is by documenting data originating from the company's annual report which is downloaded on the IDX and company websites. The analytical technique used in this research is multiple linear regression analysis. Through this study, it can be said that firm size and profitability have a positive effect on earnings management, but institutional ownership has no effect on earnings management. Keywords: Firm Size, Institutional Ownership, Profitability and Earnings Management